Proceedings of the 5th International Conference on 3D Body Scanning Technologies, Lugano, Switzerland, 21-22 October 2014 2014
DOI: 10.15221/14.093
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Foot Sizing System for Malaysian Women

Abstract: In this study we used the INFOOT USB 3D scanning system (I-Ware Laboratory Co., Ltd, Japan) to collect foot size data measurement. Based on this study, we used five measurement definitions based on their anatomical landmarks: foot length, ball girth, instep length, foot breadth, and fibulare instep length. The reliability and accuracy of the observers were evaluated using intra-and inter-observer errors measurement. Accuracy of the measurement is based on Technical Error Measurement (TEM). A TEM value of less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…One survey done by Shariff et al [19] found that 60% of Malaysian women did not have enough choices in choosing shoe size while 66.3% were dissatisfied and faced difficulties in choosing the right shoe size. The survey also shows that more than two-thirds of the sample thought that Malaysia should have a newly-developed standard for shoe sizing.…”
Section: Introductionmentioning
confidence: 99%
“…One survey done by Shariff et al [19] found that 60% of Malaysian women did not have enough choices in choosing shoe size while 66.3% were dissatisfied and faced difficulties in choosing the right shoe size. The survey also shows that more than two-thirds of the sample thought that Malaysia should have a newly-developed standard for shoe sizing.…”
Section: Introductionmentioning
confidence: 99%